البرامج اللغوية فى الطالبات الجديدات لتعليم مهارة الكلام بمعهد الإسلامي المنورة جومبانج - Lailatul Fitroh; Isniayatun Niswah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
This study aims to determine the language program for new students in improving speaking skills and to find out the supporting and inhibiting factors in this program. This language program integrates several learning stages such as opening, core activities, and closing. This research method uses qualitative research. Data were collected through observation, interview and documentation. The results show that this language program uses Arabic conversation books and Arabic Qowa'id. This language learning is carried out three times a week with supporting factors, namely, the strong enthusiasm of students, a supportive environment, teachers come from cottage graduates and the existence of bound rules. Then the inhibiting factors are, different student backgrounds, lack of innovation and utilization of learning media, and limited time. The discussion in the language program includes a series of language learning for new students to improve speaking skills.